Co-offending among outlaw motorcycle gang members: The role of social and geographical proximity - van Deuren, Sjoukje; Diviák, Tomáš; Blokland, Arjan (Journal of criminal justice, 2025)
Members of outlaw motorcycle gangs (OMCGs) have been shown to be disproportionally engaged in criminal behavior, including serious and organized crime. Fellow OMCG members have furthermore been found to facilitate this criminal behavior both indirectly, by providing a moral climate and opportunity structure conducive to crime, and directly, by acting as co-offenders. Although co-offending among OMCG members is prevalent, the driving factors in OMCG members' co-offender choice remain largely unknown. In the present study, we examine whether co-offending among OMCG members is best explained by social proximity, measured here as similarity in age and rank within the club, and shared club and chapter membership, or rather by geographical proximity, measure here as the distance (in kilometers) between chapters' clubhouses. To examine the driving factors of OMCG members' co-offending we apply the recently developed Poisson Quadratic Assignment Procedure regression on the officially registered co-offending data of a sample of 1096 members of four of the most notorious Dutch OMCGs. This study examines co-offending of OMCG members in general and for organized, violent and property crime in particular. The results show that in their choice of co-offenders, social rather than geographical proximity predicts the frequency of co-offending among OMCG members.